Água ozonizada como solução de limpeza dentinária: ação antibacteriana e análise da resistência de união - Laurindo, Brenda Matsunaga (2019)
The objective of this work was to evaluate the antibacterial activity of ozonated water on the microorganisms Streptococcus mutans and Enterococcus faecalis and also to verify its influence on adhesive bond strength (RU), both conditions compared to 17% Trisodium EDTA; Sodium hypochlorite 2.5%; Chlorhexidine 2% and Saline. The antibacterial evaluation was carried out by the Bacterial Viability Test (TVB) on the microorganisms E. faecalis and S. mutans, in the times: T0 (soon after the bacterial inoculum placement); T10 (10min), T20 (20min), T30 (30min) and T60 (60min). For UK, 50 crowns of bovine teeth were divided and divided according to the cavity cleaning material. Three bulk fill resin cylinders were made for each bovine crown and the test was performed after 24 hours. The failure modes were evaluated with stereoscopic loupes with a 40x magnification. The data were analyzed statistically by the ANOVA test and Tukey's post-test with a significance level of p <0.05. All solutions tested showed antibacterial activity, except SF. For UK there were no significant differences between groups. It can be concluded that ozonated water may be an option as a dentin cleaning solution without interfering with bond strength.